2004
DOI: 10.1021/jf0303114
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Evaluation in Dessert Spices Compared with Common Food Additives. Influence of Irradiation Procedure

Abstract: The antioxidant properties of seven dessert spices (anise, cinnamon, ginger, licorice, mint, nutmeg, and vanilla) were compared with those of the common food antioxidants butylated hydroxyanisole (BHA) (E-320), butylated hydroxytoluene (BHT) (E-321), and propyl gallate (E-310). The influence of irradiation process on antioxidant activity was also evaluated. Mint and cinnamon exhibited a higher percentage of inhibition of oxidation than the other spices analyzed and the food antioxidants, as tested by the lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(119 citation statements)
references
References 53 publications
5
100
0
5
Order By: Relevance
“…Irradiation also did not influence the antioxidant activities of cinnamon to a great extent, although a small decrease was observed in the range of 20 -25 kGy [24]. Murcia et al [25] carried out quantitative evaluation of antioxidant capacity based on Trolox Equivalent Antioxidant Capacity (TEAC) that can be used to provide a ranking order of antioxidants. They have also observed that, the irradiated samples did not show differences from non-irradiated ones in TEAC values.…”
Section: Resultsmentioning
confidence: 99%
“…Irradiation also did not influence the antioxidant activities of cinnamon to a great extent, although a small decrease was observed in the range of 20 -25 kGy [24]. Murcia et al [25] carried out quantitative evaluation of antioxidant capacity based on Trolox Equivalent Antioxidant Capacity (TEAC) that can be used to provide a ranking order of antioxidants. They have also observed that, the irradiated samples did not show differences from non-irradiated ones in TEAC values.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments adopted to verify antioxidant activity of non-polar extracts and compounds (Murcia et al, 2004) must be used to obtain real conclusions about the antioxidant activity of M. imbricata non polar constituents.…”
Section: Resultsmentioning
confidence: 99%
“…Both CTC and MPC in all concentrations tested shown FRS activity Antioxidant activity of Maytenus imbricata Mart., Celastraceae superior to BHA (100 ppm) and GA (100 ppm) (Table 6 and 7). Phenolic compounds represent one of the greater groups of bioactive compounds encountered in vegetable kingdom (Li et al, 2006) and many of them shown antioxidant activity observed through different assays (Murcia et al, 2004;Kranl et al, 2005;Carvalho et al, 2008). Correlations between the antioxidant compound content in the material submitted to tests and the antioxidant activity are not easy to explain only using quantitative analyses (Capecka et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Cinnamon (C. zeylanicum, Family Lauraceae) is a popular flavoring ingredient, widely used in food products. It has exhibited beneficial properties to health, such as antimicrobial activity, for controlling glucose intolerance and diabetes, inhibiting the proliferation of various cancer cell lines and for treating the common cold (18,19) . In Eastern and Western folk medicine it is used for treating abdominal and chest pains, chronic diarrhea, hypertension, kidney disorders and rheumatism.…”
Section: Profenofos O-[4-bromo-2-chlorophenyl] O-ethyl S-propyl Phosmentioning
confidence: 99%